2005
DOI: 10.1007/s00425-004-1455-7
|View full text |Cite
|
Sign up to set email alerts
|

Ear of durum wheat under water stress: water relations and photosynthetic metabolism

Abstract: The photosynthetic characteristics of the ear and flag leaf of well-watered (WW) and water-stressed (WS) durum wheat (Triticum turgidum L. var. durum) were studied in plants grown under greenhouse and Mediterranean field conditions. Gas exchange measurements simultaneously with modulated chlorophyll fluorescence were used to study the response of the ear and flag leaf to CO2 and O2 during photosynthesis. C4 metabolism was identified by assessing the sensitivity of photosynthetic rate and electron transport to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
159
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 51 publications
11
159
0
5
Order By: Relevance
“…This variation may be due to leaf assimilation ability restrained with vegetative growth at jointing stage, but the nutrient in the vegetative organs start to transport for reproductive growth, thus leaf assimilation ability raise. Tambussi et al (2005) indicated that the photosynthesis after anthesis and during grain filling play important role for the final grain yield. The wide-narrow planting pattern improved leaf photosynthesis by changing the local farmland microclimate (Fernado et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This variation may be due to leaf assimilation ability restrained with vegetative growth at jointing stage, but the nutrient in the vegetative organs start to transport for reproductive growth, thus leaf assimilation ability raise. Tambussi et al (2005) indicated that the photosynthesis after anthesis and during grain filling play important role for the final grain yield. The wide-narrow planting pattern improved leaf photosynthesis by changing the local farmland microclimate (Fernado et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Siliques have stomata [105] and carry out photosynthesis [106], and apparently transpire [107], as do glumes of wheat [108,109]. Thus, the potential for xylem transport of micronutrients directly to these seed covering tissues exists.…”
Section: Translocation To Leaf or Seed Covering Tissuesmentioning
confidence: 99%
“…Then the leaves were quickly and carefully dried with filter paper to determine turgid weight (TW). Dry weight (DW) was obtained after oven-drying the leaf samples for 72 h at 70 C. RWC was calculated from the equation of Tambussi et al [25]:…”
Section: Determination Of Relative Water Content (Rwc)mentioning
confidence: 99%